High CD44 expression mediates p62-associated NFE2L2/NRF2 activation in breast cancer stem cell-like cells: Implications for cancer stem cell resistance - In-geun Ryoo; Bo-Hyun Choi; Sae‐Kwang Ku; Mi‐Kyoung Kwak (2018)
Cluster of differentiation 44 (CD44) is the most common cancer stem cell (CSC) marker and high CD44 expression has been associated with anticancer drug resistance, tumor recurrence, and metastasis. In this study, we aimed to investigate the molecular mechanism by which CD44 and nuclear factor erythroid 2-like 2 (NFE2L2; NRF2), a key regulator of antioxidant genes, are linked to CSC resistance using CD44high breast CSC-like cells. NRF2 expression was higher in CD44high cell populations isolated from doxorubicin-resistant MCF7 (ADR), as well as MCF7, MDA-MB231, and A549 cells, than in corresponding CD44low cells. High NRF2 expression in the CD44highCD24low CSC population (ADR44P) established from ADR cells depended on standard isoform of CD44. Silencing of CD44 or overexpression of CD44 resulted in the reduction or elevation of NRF2, respectively, and treatment with hyaluronic acid, a CD44 ligand, augmented NRF2 activation. As functional implications, NRF2 silencing rendered ADR44P cells to retain higher levels of reactive oxygen species and to be sensitive to anticancer drug toxicity. Moreover, NRF2-silenced ADR44P cells displayed tumor growth retardation and reduced colony/sphere formation and invasion capacity. In line with these, CD44 significantly colocalized with NRF2 in breast tumor clinical samples. The molecular mechanism of CD44-mediated NRF2 activation was found to involve high p62 expression. CD44 elevation led to an increase in p62, and inhibition of p62 resulted in NRF2 suppression in ADR44P. Collectively, our results showed that high CD44 led to p62-associated NRF2 activation in CD44high breast CSC-like cells. NRF2 activation contributed to the aggressive phenotype, tumor growth, and anticancer drug resistance of CD44high CSCs. Therefore, the CD44-NRF2 axis might be a promising therapeutic target for the control of stress resistance and survival of CD44high CSC population within breast tumors.